2020
DOI: 10.1109/access.2020.3012520
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Piezo on Single-Crystal Silicon Reactive Etched RF MEMS Resonators

Abstract: This paper demonstrates how a single crystal silicon wafer can be used to fabricate thin-film piezoelectric-on-silicon (TPoS) resonators by utilizing a modified version of Single Crystal Silicon Reactive Etch and Metallization (SCREAM) process. The developed process enables the fabrication of MEMS resonators with varied device layer thicknesses ranging from sub-micrometer to tens of micrometers (one thickness per die) from a single bulk silicon wafer, while avoiding the need of costly silicon-on-insulator (SOI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Thereafter, the fourth mask is used to generate an opening for the release process while protecting the devices. Finally, resonators are suspended by an isotropic dry etching of the amorphous Si sacrificial layer ( Figure 2 d) [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, the fourth mask is used to generate an opening for the release process while protecting the devices. Finally, resonators are suspended by an isotropic dry etching of the amorphous Si sacrificial layer ( Figure 2 d) [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pt top elect are defined via a lift-off process using the third mask (Figure 2c). Thereafter, the mask is used to generate an opening for the release process while protecting the de Finally, resonators are suspended by an isotropic dry etching of the amorphous Si s cial layer (Figure 2d) [23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin-film piezoelectric-on-substrate (TPoS) resonators based on ZnO have a considerable prospect to be used in mass or gas sensing applications. TPoS resonators are strategically coupled with low loss substrates like Si to have higher acoustic velocities and to store more energy which results in increasing the equivalent acoustic velocity to be higher than typical piezoelectric resonators [15]. Based on a previous study [16], the effects of mass loading on TPoS based resonators have shown high sensitivity of the first and fourth-order contour mode ZnO-on-Si MEMS resonator-based mass sensor, which provides massive potential in mass sensing applications.…”
Section: Piezoelectric Humidity Sensing Technologymentioning
confidence: 99%
“…DRIE etching has developed to the point where the etch rates are sufficient for production [ 35 ]. DRIE is now commonly used for bulk micromachining of single-crystal silicon for a wide range of applications—inertia sensors [ 47 , 48 , 49 , 50 , 51 ], pressure sensors [ 52 , 53 , 54 ], microphones [ 55 ], resonators [ 56 ], microfluidics [ 57 , 58 , 59 ], and others [ 60 , 61 ].…”
Section: Bosch Tm Driementioning
confidence: 99%